Indigenous Higher Education: The Role of Universities in Releasing the Potential - Andersen, Clair; Bunda, Tracey; Walter, Maggie (The Australian Journal of Indigenous Education, 2008)
Abstract The participation rate of Indigenous people in higher education is comparatively disparately low across all sectors. In this paper we examine the pivotal role of the university sector in addressing this inequity and releasing the potential for increased Indigenous enrolment, participation and completion in higher education. Indigenous higher education, we argue, is core university business, not an equity issue, and a unique opportunity currently exists for achieving significant progress. Using examples of best practice we show how universities can take positive practical steps to overcome the commonly identified barriers to Indigenous higher education success. We also propose four specific strategies for increasing Indigenous higher education success across all facets. We extend our analysis to the low Indigenous representation among university staff arguing that a greater presence and nurturing of Indigenous staff, academic and general is a vital facet of improving Indigenous higher education access and success. Finally, we argue that a longitudinal study of Indigenous higher education participation is needed to provide an evidence base to inform and increase the efficacy of policy in this area.